1983
DOI: 10.1111/j.1752-1688.1983.tb04592.x
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Water Yield Augmentation From Forest Management in the Eastern United States1

Abstract: Generally high rainfall and extensive forests in the East combine to produce excellent potential for managing forests for increased water yield. Models are presented that allow prediction of streamflow increase from hardwood and pine forests on a year-by-year basis. They are being routinely applied in land management planning on National Forests in the Southeast. A recent, independent test indicates that cumulative water yield increases can be predicted within about 14 percent of the actual value. However, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 8 publications
(5 reference statements)
1
40
0
Order By: Relevance
“…The results suggested that higher stand age is associated with lower water yield. This can be explained by basal area and LAI, which affect water yield, since both increase as a forest becomes older [17,21,49,51]. Our findings also show that slash pine stands managed under private ownership tended to have higher water yield than their counterparts managed under public land tenure.…”
Section: Management Implicationsmentioning
confidence: 50%
“…The results suggested that higher stand age is associated with lower water yield. This can be explained by basal area and LAI, which affect water yield, since both increase as a forest becomes older [17,21,49,51]. Our findings also show that slash pine stands managed under private ownership tended to have higher water yield than their counterparts managed under public land tenure.…”
Section: Management Implicationsmentioning
confidence: 50%
“…These vegetative communities are situated on sites with ''favorable precipitation regimes'' and, in the case of the chaparral shrublands, found close to downstream points of water consumption; therefore, in this latter case, en-route transmission losses are lessened DeBano et al, 2004;Stednick and Troendle, 2004). However, estimates of increases in streamflow following implementation of vegetative management practices in the Colorado River Basin and elsewhere generally refer to on-site responses at the outlet of the upland watersheds (Bosch and Hewlett, 1982;Douglas, 1983;Hibbert, 1979Hibbert, , 1983Hornbeck et al, 1993;Whitehead and Robinson, 1993). It is important to point out that the area of such vegetation is less than 9 million ha or about 14% of the total area of the basin.…”
Section: Discussionmentioning
confidence: 98%
“…Historically, the more common goal of forest management has been for the purpose of increasing water yield rather than flood control (Hursh, 1951;Douglass and Swank, 1972;Douglass, 1983;Hibbert, 1983;Krutilla et al, 1983;Ponce and Meiman, 1983). The lack of emphasis on flooding is not due to a lack of interest, but rather opportunity and the complexity of the issue.…”
Section: Summary Of Published Researchmentioning
confidence: 96%